Arduino-Based Automatic Door Opener Design Using Ultra-sonic Sensors - Desriani Martha Noelita Pakpahan; Hari Purwadi; Agusma Wajiansyah (Journal of Engineering, Electrical and Informatics, 2026)
The development of microcontroller technology has made it easier to design simple, economical, and easily applied automatic systems in everyday life. One application of this technology is an automatic door opener system. This study aims to design and test an Arduino-based automatic door opener system using an HC-SR04 ultrasonic sensor as an object detector. A cardboard house is used as a prototype to simplify the system design and testing process. The designed system uses an Arduino Uno as the main controller, an HC-SR04 ultrasonic sensor as a distance detector, and a servo motor as an actuator to open and close the door. The ultrasonic sensor detects the distance of the object in front of the door, then the Arduino processes the distance data to determine whether the door will open or close automatically. Tests were conducted with several variations in object distance to determine the level of sensor accuracy and system response. The test results show that the system is able to work well at a detection distance of less than or equal to 15 cm with an average response time of around 0.8 – 1.0 seconds. The door can open automatically when the object is within a predetermined distance and closes again after the object moves away. Based on these results, the designed automatic door opening system can function according to the research objectives and is suitable for application in a door automation system prototype.